2015
DOI: 10.1002/humu.22819
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon Resequencing Identified Parental Mosaicism for Approximately 10% of “ de novoSCN1A Mutations in Children with Dravet Syndrome

Abstract: The majority of children with Dravet syndrome (DS) are caused by de novo SCN1A mutations. To investigate the origin of the mutations, we developed and applied a new method that combined deep amplicon resequencing with a Bayesian model to detect and quantify allelic fractions with improved sensitivity. Of 174 SCN1A mutations in DS probands which were considered “de novo” by Sanger sequencing, we identified 15 cases (8.6%) of parental mosaicism. We identified another five cases of parental mosaicism that were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 64 publications
10
115
0
Order By: Relevance
“…All cases were confirmed in a maternally inherited pattern sharing an identical mutation with their mothers while no mutations in their father. Additionally, we confirmed no existence of a mosaic mutation in their parents using digital PCR and PGM (Xu et al, 2015). The phenotypes of the three female patients were consistent with those of RTT but the five males not.…”
Section: Discussionsupporting
confidence: 77%
“…All cases were confirmed in a maternally inherited pattern sharing an identical mutation with their mothers while no mutations in their father. Additionally, we confirmed no existence of a mosaic mutation in their parents using digital PCR and PGM (Xu et al, 2015). The phenotypes of the three female patients were consistent with those of RTT but the five males not.…”
Section: Discussionsupporting
confidence: 77%
“…No validation studies were performed, which may have led to false positive results; however, as the reported percentages of mosaicism were relatively high (16.7%–30.6%), this risk may be low. Xu et al 20 found parental mosaicism in 10% of Dravet syndrome families as well. Yang et al 21 reported an even higher incidence: parental mosaicism was detected in 25% of Dravet syndrome families.…”
Section: Discussionmentioning
confidence: 95%
“…These genes included SCN1A in 3 of 40 families with apparently de novo SCN1A mutations; these findings showing that approximately 10% of children with an apparently de novo SCN1A variant had a parent with mosaicism replicated those of another study. 5 In addition, one variant occurred in each of the following genes: SCN8A, GNB1, SLC6A1, DNM1, KCNT1, CACNA1A , and KCNQ2 . Owing to the small sample size, we were unable to determine whether certain genes, such as those encoding ion channels, were more prone to mosaicism.…”
Section: To the Editormentioning
confidence: 99%